Outgrowing resource dependence : theory and some recent developments - Martin, Will, 1953- 1953- (Policy research working paper, 2005)
"Many policymakers are concerned about dependence on resource exports. Martin examines four changes that reduce this dependence: (1) accumulation of capital and skills; (2) changes in protection policy, particularly reductions in the burden of protection on exporters;(3) differential rates of technical change; and (4) declines in transport costs. Developing countries as a group have made enormous progress in diversifying their exports away from resources in recent decades, a development that appears to have been aided by accumulation of capital and skills and by dramatic reductions in the cost of protection to exporters, but slowed down by technological advances that favored agriculture. This paper--a product of the Trade Team, Development Research Group--is part of a larger effort in the group to understand the links between trade and economic development"--World Bank web site